Determining protein polarization proteome-wide using physical dissection of individual Stentor coeruleus cells - Lin, Athena; Piehowski, Paul D; Tsai, Chia-Feng; Makushok, Tatyana; Yi, Lian; Diaz, Ulises; Yan, Connie; Summers, Diana; Sood, Pranidhi; Smith, Richard D; Liu, Tao; Marshall, Wallace F (Current biology, 2022)
Cellular components are non-randomly arranged with respect to the shape and polarity of the whole cell. Patterning within cells can extend down to the level of individual proteins and mRNA. But how much of the proteome is actually localized with respect to cell polarity axes? Proteomics combined with cellular fractionation has shown that most proteins localize to one or more organelles but does not tell us how many proteins have a polarized localization with respect to the large-scale polarity axes of the intact cell. Genome-wide localization studies in yeast found that only a few percent of proteins have a localized position relative to the cell polarity axis defined by sites of polarized cell growth. Here, we describe an approach for analyzing protein distribution within a cell with a visibly obvious global patterning-the giant ciliate Stentor coeruleus. Ciliates, including Stentor, have highly polarized cell shapes with visible surface patterning. A Stentor cell is roughly 2 mm long, allowing a "proteomic dissection" in which microsurgery is used to separate cellular fragments along the anterior-posterior axis, followed by comparative proteomic analysis. In our analysis, 25% of the proteome, including signaling proteins, centrin/SFI proteins, and GAS2 orthologs, shows a polarized location along the cell's anterior-posterior axis. We conclude that a large proportion of all proteins are polarized with respect to global cell polarity axes and that proteomic dissection provides a simple and effective approach for spatial proteomics.